Thermal and Hydrodynamic Performance Analysis of a Shell and Tube Heat Exchanger Using the AHP Multicriteria Method - Ravelo Mendivelso Karol Yuliete; Villate Mercy Tatiana; Hernandez, José D.; Miranda, Orlando M.; Pacheco, Pedro J.; Campusano, Manuel J. (Universidad Antonio Nariño, 2023)
Abstract. The goal of this work is to identify the best alternatives that allow for improving the thermal efficiency of a shell and tube heat exchanger in real operating conditions. The main motivation for carrying out the research is based on the need identified, together with the oil, natural gas, and alternative energy industry, to analyze and learn about the main criteria that directly impact the thermal efficiency of a heat exchanger. The applied methodology was based on the AHP (Analytic Hierarchy Process) multicriteria method. Three relevant criteria were identified: Thermodynamic, Hydrodynamic, and Economic. Additionally, a complete analysis of 9 sub-criteria (i.e. energy and exergetic analysis of the process, analysis of the thermodynamic properties of the fluids; pressure drop, volumetric flow of hot and cold fluids; energy costs, maintenance, operation and geometry of the heat exchanger) allowed us to conclude that the best strategy to increase the thermal efficiency of a heat exchanger in real operating conditions consists of using innovative online cleaning prototypes that use abrasive spheres. This will allow the heat exchanger to be cleaned simultaneously with its operation, reducing downtime and maintenance times/costs.